Baron Cohen on autism core studies in psychology - Cohen, Simon Baron (Australia : VEA, 2010)
Simon Baron Cohen is a world figure in psychology and autism in particular. Proffessor of Development Psychopathology in the Departments of Psychiatry and Experimental Psychology at the Unverisity of Cambridge, he is the Director of the University's Autism Research Centre, and also a Fellow College. In this program Baron Cohen disscuses his case study,'Another Advanced Test of Theory of Theory of Mind'. Cohen explain the aims and origins of his study, illustrates his'Eyes Test' methodology, explaning why the eyes were chosen, and talks about his findings and their implications for understanding autism. The DVD intercut with illustrative footage of autistic children, their parents and autistic adults.
DVD format.
System requirements : progressive scan DVD player.
Keywords: Autism